Variabilidade do Índice de vegetaÇÃo por diferenÇa normalizada (NDVI) em Áreas de reflorestamento: Floresta estadual ‘edmundo navarro de andrade’ (feena)/rio claro (SP) - Castanheira, Luiz Batista [UNESP]; Milton Barbosa Landim, Paulo [UNESP]; Lourenço, Roberto Wagner [UNESP] (My University, 2014)
This research presents a qualitative analysis of the density and intensity of vegetation photosynthetic activity with possible consequences on carbon flux in the region of the State Forest Edmundo Navarro de Andrade (FEENA), through the variation of the Normalized Difference Vegetation Index (NDVI). Most of the FEENA, which is a Conservation Unit, is located in the area of the municipality of Rio Claro. Rio Claro is located in the Center-East of the State of São Paulo, between the coordinates 22°05' South Latitude and 47°55' West Longitude of Greenwich. In the analysis, images from Landsat 5 TM sensor from 1985 to 2011. The analysis took into account Descriptive Statistics measures of central tendency and dispersion of NDVI, besides trend curves. Geographical Information Systems (GIS) and spreadsheets were used as tools. The time series NDVI maps of FEENA showed full range 0.05 and overall average 0.68. These values indicate that high density and high intensity of photosynthetic activity of forest vegetation were stable during this period. Because of this, it can be inferred that increase of carbon sequestration from the atmosphere in the region occurred.
Keywords: FEENA; NDVI; Reforestation; Remote Sensing